Technique adaptation at varying friction in cross-country ski skating - Hindér, G.; Vieider, M. A.; Sandberg, J.; Almqvist, A.; Larsson, R. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The varying snow conditions in cross-country skiing races lead to significant changes in the resistive forces caused by ski-snow friction. Previous studies have examined how this affects skiers while skating on snow [1,2] and roller skis on a treadmill [3], but somewhat conflicting results have emerged. A common factor in these studies is that skier velocity was restricted. This study aims to investigate how cross-country skiers adjust their technique across varying resistive forces, on both traditional and roller skis, using perceived exertion and heart rate as a controlled factor to simulate a race-like situation.